2016
DOI: 10.1073/pnas.1604849113
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function at RAE2 , a previously unidentified EPFL, is required for awnlessness in cultivated Asian rice

Abstract: Domestication of crops based on artificial selection has contributed numerous beneficial traits for agriculture. Wild characteristics such as red pericarp and seed shattering were lost in both Asian (Oryza sativa) and African (Oryza glaberrima) cultivated rice species as a result of human selection on common genes. Awnedness, in contrast, is a trait that has been lost in both cultivated species due to selection on different sets of genes. In a previous report, we revealed that at least three loci regulate awn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 39 publications
4
100
1
Order By: Relevance
“…To determine the functional variation regulating awn formation on the basis of significant SNP/InDels, we classified the sequences of rice accessions into haplotypes An‐hap1, An‐hap2, An‐hap3 and An‐hap4. Comparing the numbers of cysteines (C) in GLA (Bessho‐Uehara et al ., ) it became evident that An‐hap1 and An‐hap2 were 6C type, whereas An‐hap3 and An‐hap4 were 7C and 4C types respectively. The rare SNP1 variant in An‐hap1 occurred only in japonica .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…To determine the functional variation regulating awn formation on the basis of significant SNP/InDels, we classified the sequences of rice accessions into haplotypes An‐hap1, An‐hap2, An‐hap3 and An‐hap4. Comparing the numbers of cysteines (C) in GLA (Bessho‐Uehara et al ., ) it became evident that An‐hap1 and An‐hap2 were 6C type, whereas An‐hap3 and An‐hap4 were 7C and 4C types respectively. The rare SNP1 variant in An‐hap1 occurred only in japonica .…”
Section: Resultsmentioning
confidence: 95%
“…Amino acid sequence analysis indicated that the InDel3 deletion caused a premature stop codon and truncated protein (Figure S4). LOC_Os08 g37890 is the same locus as Hap.A/B/C (Yano et al ., ), GAD1 (Jin et al ., ) and RAE2 (Bessho‐Uehara et al ., ; Jin et al ., ; Yano et al ., ) that belong to the epidermal patterning factor‐like protein (EPFL) family and regulate awn development. Thus, LOC_Os08 g37890 was postulated to be the most likely candidate gene for GLA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asian and African rice were domesticated independently (Vaughan et al, ), and awn loss is likely due to changes at separate loci. QTL analyses show that awn loss in African rice is under the control of an independent locus to An‐1 , as African rice has functional copies of both An‐1 and RAE2/GAD1 (Furuta et al, ; Bessho‐Uehara et al, ). There is also evidence for independent loci controlling the development of barbed rice awns.…”
Section: Organ Diversification: Lemma Awnsmentioning
confidence: 99%
“…This result indicates that the critical mutation may have arisen independently in China and in the Himalayas (Yuo et al, ). Similarly, RAE2/GAD1 has likely been repeatedly inactivated in Asian rice cultivars (Bessho‐Uehara et al, ). These results demonstrate that awn development and evolution can have a complex history, even within a single genus.…”
Section: Organ Diversification: Lemma Awnsmentioning
confidence: 99%